CARRENT ISSUES OF SOCIAL AND PSYCHOLOGICAL PROTECTION OF CHILDREN LEFT WITHOUT PARENTAL CARE - Sulaymanova Dildora Kodirovna (FAN, TA’LIM VA AMALIYOT INTEGRATSIYASI, 2021)
Although the guardianship and trusteeship role study in the children social protection left without parental care has not been studied as a single comprehensive study, however, the issues related to or around it have been reflected to some extent in many scientific research works of foreign and domestic scientists. At the same time, this issue also reveals the problem urgency